Utility of Elevated Pentraxin-3 Level as Inflammatory Marker for Predicting Adverse Outcomes in Patients With Acute Coronary Syndrome: A Meta-Analysis - Fan, Yu; He, Rong; Man, Changfeng; Gong, Dandan (Frontiers in Cardiovascular Medicine, 2022)
Background: Vascular inflammation plays an important role in the pathogenesis and development of acute coronary syndrome (ACS). However, studies on the association between elevated pentraxin-3 level and adverse outcomes in patients with ACS have yielded controversial results. The purpose of this meta-analysis was to assess the value of elevated pentraxin-3 level as an inflammatory marker for predicting adverse outcomes in ACS patients. Methods: Two authors systematically searched the articles indexed in PubMed, Embase, CNKI, Wanfang, and VIP databases up to March 31, 2021. Studies reporting the association of elevated pentraxin-3 level at the acute phase with cardiovascular mortality, all-cause mortality, or cardiac events (cardiac death, nonfatal myocardial infarction, revascularization, or heart failure) in ACS patients were included. Results: A total of 8775 ACS patients from 12 studies were identified and analyzed. When compared the lowest pentraxin-3 level, ACS patients with the highest pentraxin-3 level conferred an increased risk of cardiovascular mortality (risk ratio [RR] 2.10; 95% confidence intervals [CI] 1.44–3.06), all-cause mortality (RR 1.99; 95% CI 1.46–2.71), and cardiac events (RR 1.74; 95% CI 1.32–2.29), even after adjustment for some important confounders. Subgroup analysis indicated that the association of elevated pentraxin-3 level with cardiac events appeared to be stronger in ST-segment elevation myocardial infarction patients (RR 2.72; 95% CI 1.69–4.36) than in all ACS patients (RR 1.59; 95% CI 1.10–2.29). Conclusions: Elevated pentraxin-3 level is possibly an independent predictor of adverse outcomes in patients with ACS. Assessment of pentraxin-3 level at the acute phase can provide important information for early risk stratification of ACS.